STUNTING AND OBESITY PREVENTION EDUCATION AT PARENTS OF PAUD STUDENTS ON THE COMMEMORATIONOF NATIONAL NUTRITION DAY: EDUKASI PENCEGAHAN STUNTING DAN OBESITAS PADA ORANGTUA SISWA PAUD PADA PERINGATAN HARI GIZI NASIONAL - Ratih Damayanti; Anita Dewi Moelyaningrum; Inar Garmarini (Darmabakti Cendekia: Journal of Community Service and Engagements, 2023)
Background: Indonesia is experiencing a double burden of nutrition because at this time there are still malnutrition problems, one of which is stunting and also over nutrition problems, namely obesity in children. Objective: The purpose of this community service activity is to increase the knowledge of parents/guardians of TK/KB Lasiyam Surabaya students about "Actions to Prevent Stunting and Obesity in Children". Method: Online education with webinar format targeting parents of TK/KB Lasiyam students, Surabaya. Then at the end of the activity, participants were given a post test questionnaire to find out the results of understanding the material "Joint action to prevent stunting and obesity in children". Results: The majority of participants are aged 25-35 years with a diploma/bachelor degree and working as private employees. 78% of participants in this webinar-based education have a good level of knowledge after attending the webinar. Conclusion: Parents of TK/KB Lasiyam Surabaya students have a good level of knowledge so it is hoped that stunting and obesity can be suppressed, one of which is through early childhood education institutions.